Dilema Kedaulatan Maritim: Analisis Dampak Strategis Wacana Tarif Selat Malaka terhadap Legitimasi Indonesia sebagai Negara Kepulauan - Nyakdhien Sachari (Jurnal Ilmu Sosial dan Humaniora, 2026)
The Strait of Malacca is one of the most strategically significant international shipping lanes in the world, connecting the Indian Ocean to the South China Sea. This geographical position places Indonesia within a persistent structural tension between the pursuit of national maritime sovereignty and its binding international obligations as an archipelagic state under UNCLOS 1982. This study examines the strategic implications of the discourse surrounding the proposed imposition of transit fees on foreign vessels in the Strait of Malacca, which emerged in April 2026, and its effects on Indonesia’s maritime legitimacy. Employing a qualitative descriptive-analytical approach through library research, this study analyzes the issue using three theoretical frameworks: Realism, Liberal Institutionalism, and the Copenhagen School’s securitization theory. The findings reveal that the tariff discourse simultaneously reflected national interest maximization and exposed the limits of domestic jurisdiction under international maritime law. An exploratory statement by a state official proved sufficient to trigger global securitization dynamics, even without constituting formal policy. Multilateral burden-sharing mechanisms under Article 43 of UNCLOS are identified as a more sustainable and legally tenable avenue compared to unilateral fiscal regulation. This study concludes that Indonesia’s legitimacy as a responsible archipelagic state fundamentally depends on its consistent adherence to international maritime norms and careful management of public policy communication.